Imaging performance of phase-contrast breast computed tomography with synchrotron radiation and a CdTe photon-counting detector. Issue 5 (May 2016) - Sarno, A.; Mettivier, G.; Golosio, B.; Oliva, P.; Spandre, G.; Di Lillo, F.; Fedon, C.; Longo, R.; Russo, P.
Abstract : Highlights: The imaging performance of a phase-contrast breast CT was assessed. Monochromatic synchrotron radiation for breast CT was used. A high-spatial resolution, single-photon counting CdTe detector was adopted. Phase-retrieved images showed the best performance. Abstract: Purpose: Within the SYRMA-CT collaboration based at the ELETTRA synchrotron radiation (SR) facility the authors investigated the imaging performance of the phase-contrast computed tomography (CT) system dedicated to monochromatic in vivo 3D imaging of the female breast, for breast cancer diagnosis. Methods: Test objects were imaged at 38 keV using monochromatic SR and a high-resolution CdTe photon-counting detector. Signal and noise performance were evaluated using modulation transfer function (MTF) and noise power spectrum. The analysis was performed on the images obtained with the application of a phase retrieval algorithm as well as on those obtained without phase retrieval. The contrast to noise ratio (CNR) and the capability of detecting test microcalcification clusters and soft masses were investigated. Results: For a voxel size of (60 μm) 3, images without phase retrieval showed higher spatial resolution (6.7 mm −1 at 10% MTF) than corresponding images with phase retrieval (2.5 mm −1 ). Phase retrieval produced a reduction of the noise level and an increase of the CNR by more than one order of magnitude, compared to raw phase-contrast images. Microcalcifications with a diameter down to 130 μm could be detected in both types of images. Conclusions: The investigation on test objects indicates that breast CT with a monochromatic SR source is technically feasible in terms of spatial resolution, image noise and contrast, for in vivo 3D imaging with a dose comparable to that of two-view mammography. Images obtained with the phase retrieval algorithm showed the best performance in the trade-off between spatial resolution and image noise.